A quantification of classic but unquantified positive feedback effects in the urban-building-energy-climate system. (1st February 2022) - Kikegawa, Yukihiro; Nakajima, Kazusa; Takane, Yuya; Ohashi, Yukitaka; Ihara, Tomohiko
Highlights: Feedback effects in the urban building energy and climate system were quantified. Fed-back gains in cooling energy demand reaching 10% were estimated in Osaka. The proposed urban meteorological model WRF-CM-BEM can reproduce the above effect. The model estimated fed-back impacts on air temperature of 10 to 20%. Abstract: The interaction between urban air temperature ( T ) and building cooling energy demand ( E ) generates a well-known positive feedback (PFB), which is mediated by sensible anthropogenic heat ( Qfs ) and named Qfs -T-E PFB in this study. This PFB could induce self-reinforced warming in urban areas, but its effects have not been completely quantified. Hence, this study aimed to clarify these effects by targeting Osaka, a Japanese major city. Focusing on the from-weekends-to-weekdays increase in urban energy consumption including E increase as an observable trigger of the PFB, its induced T rise due to growth in Qfs was estimated with the fed-back additional E gain on weekdays based on observed ground-level T and district-wise electric power consumption during summer. The result indicated that the weekdays–weekends contrast in energy consumption over Osaka could induce the Qfs -T-E PFB effects, which resulted in fed-back E gain reaching 10% on weekdays. Such observational PFB impact on E was found to be roughly reproducible by the proposed urban meteorological model, named WRF-CM-BEM. Thus, the validated model was applied to the quantification of the climatological PFB impact on T based on feedback gain ( gA ) which means a percentage of T variation caused by the PFB. An attempt was made to quantify gA through the two-cases simulations of the weekdays-run and holidays-run for the months of August in 10 years, focusing again on the weekdays–weekends contrast in urban energy consumption. The simulations provided estimates on gA, whose daytime averages reached nearly 10% in the downtown commercial areas and 20% in the leeward-located residential areas, suggesting the influence of sea breeze heat advection of downtown Qfs . Such estimated impacts on T were roughly in the same order of magnitude compared to those in a few earlier studies that were not based on observational validations and seemed to be non-negligible, considering the feedback impacts on global surface warming estimated with gA of approximately 50% by the Intergovernmental Panel on Climate Change.